2014
DOI: 10.1177/1947603513518216
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Clinical Outcomes Following Autogenous Bone Grafting for Large-Volume Defects of the Knee

Abstract: Objective:We report the long-term clinical outcomes of patients who underwent autogenous bone grafting of large-volume osteochondral defects of the knee due to osteochondritis dessicans (OCD) and osteonecrosis (ON). This is the companion report to one previous published on the biological response. We hypothesized that these grafts would integrate with host bone and the articular surface would form fibrocartilage providing an enduring clinical benefit.Design:Three groups (patients/knees) were studied: OCD witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This relatively high failure rate was consistent with our results that showed that 2 of 3 patients with AVN failed after ABG alone (1 patient with ACI at 5 months; the other patient with TKA at 15 years). Moreover, when considering that they treated an older population (mean age, 47 years) than our cohort (mean age, 30 years in the ACI sandwich group), ABG alone appears not to be a suitable option for young, active patients who were counseled to have lessened expectations for symptoms and activities after ABG by Johnson et al 22…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This relatively high failure rate was consistent with our results that showed that 2 of 3 patients with AVN failed after ABG alone (1 patient with ACI at 5 months; the other patient with TKA at 15 years). Moreover, when considering that they treated an older population (mean age, 47 years) than our cohort (mean age, 30 years in the ACI sandwich group), ABG alone appears not to be a suitable option for young, active patients who were counseled to have lessened expectations for symptoms and activities after ABG by Johnson et al 22…”
Section: Discussionmentioning
confidence: 74%
“…Recently, Johnson et al 22 have reported long-term outcomes after ABG for the treatment of OCD and osteonecrosis. Their cohort of patients with OCD included 2 different groups: one with ABG plus repair of the cartilage fragment and the other one with ABG without the cartilage fragment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 When the more severe pathological articular disruption of largevolume femoral defects of the knee were treated by arthroscopy, the results were similar regarding avoidance or delay of total knee surgery. 32 Even more amazing was one patient with the largest of bilateral femoral lesions. At 17 years following surgery, he had a normal range of motion of both knees and unaided normal ambulation.…”
mentioning
confidence: 98%